Diminished warming tolerance and plasticity in low-latitude populations of a marine gastropod - Villeneuve, Andrew R (Conserv Physiol, 2021)
Models of species response to climate change often assume that physiological traits are invariant across populations. Neglecting potential intraspecific variation may overlook the possibility that some populations are more resilient or susceptible than others, creating inaccurate predictions of climate impacts. In addition, phenotypic plasticity can contribute to trait variation and may mediate sensitivity to climate. Quantifying such forms of intraspecific variation can improve our understanding of how climate can affect ecologically important species, such as invasive predators. Here, we quantified thermal performance (tolerance, acclimation capacity, developmental traits) across seven populations of the predatory marine snail (Urosalpinx cinerea) from native Atlantic and non-native Pacific coast populations in the USA. Using common garden experiments, we assessed the effects of source population and developmental acclimation on thermal tolerance and developmental traits of F1 snails. We then estimated climate sensitivity by calculating warming tolerance (thermal tolerance − habitat temperature), using field environmental data. We report that low-latitude populations had greater thermal tolerance than their high latitude counterparts. However, these same low-latitude populations exhibited decreased thermal tolerance when exposed to environmentally realistic higher acclimation temperatures. Low-latitude native populations had the greatest climate sensitivity (habitat temperatures near thermal limits). In contrast, invasive Pacific snails had the lowest climate sensitivity, suggesting that these populations are likely to persist and drive negative impacts on native biodiversity. Developmental rate significantly increased in embryos sourced from populations with greater habitat temperature but had variable effects on clutch size and hatching success. Thus, warming can produce widely divergent responses within the same species, resulting in enhanced impacts in the non-native range and extirpation in the native range. Broadly, our results highlight how intraspecific variation can alter management decisions, as this may clarify whether management efforts should be focused on many or only a few populations.